ADABIY TA’LIMDA TADQIQOTCHILIK KOMPETENSIYASINI SHAKLLANTIRISHNING METODIK SHARTLARI (Konferensiyalar | Conferences, 2023)
The article covers the issue of forming research competence in students by directing them to small scientific research from school age. In particular, approaches such as the "Moment of Success" method, the formation of hypotheses and questions, are important in terms of students being able to pose a problem on the essence of a specific object, to put forward new ideas, to propose appropriate solutions based on this, and to direct them to creative research. aspects are analyzed.